Characterization of nutritional and functional properties of Lima bean flour (Phaseolus Lunatus L.). Issue 1 (November 2021) - Palupi, H T; Estiasih, T; Yunianta,; Sutrisno, A
Abstract: Lima beans ( Phaseolus Lunatus L.) are underutilized crops with an excellent profile. Processing to flour to enhance the starch and protein content, reducing anti-nutritional components and the same time diversifies their use as ingredients by altering their functional properties. The study aims to characterize nutritional, amino acids, anti-nutritional, pasting and functional properties of Lima bean flour from Indonesia's cultivated plant. The results showed that the Lima bean flour has a high carbohydrate concentration, moderate protein concentration, and low fat concentration. This flour has a balanced amino acid profile, rich in essential amino acids, highlighting them as a source of good quality protein for the food formulation of protein-enriched. The Lima bean flour contained 10.36 mg/g phytic acid, lower in phenolic content (0.63 mg/g) and concentration of HCN (8.83 mg/kg). The functional properties of the Lima bean flour swelling power, solubility, water absorption capacities, and oil absorption capacities were 6.88 g/g, 18.68%, 1.93 g/g, and 1.56 g/g respectively. Pasting properties of Lima bean flour exhibited peak, breakdown, final, and setback viscosity in 1172 cP, 83 cP, 2377 cP, 1288 cP respectively, and temperature pasting was high in 87 0 C. The study may provide useful information to consumers and food manufacturers that Lima bean flour is significant potential used to enhance the nutritional value of cereal-based foods.